PENERAPAN METODE MATERNAL REFLEKTIF (MMR) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PESERTA DIDIK DENGAN HAMBATAN PENDENGARAN: BEST PRACTICE DI SLB ISLAM QOTHRUNNADA - Aningrum, Rizki; Dewi, Galih Rasita; Irmawanti (Pimpinan Cabang Muhammadiyah Kramat Jati, 2025)
This research documents the implementation of the Reflective Maternal Method (RMM) to improve the reading comprehension skills of students with hearing impairments in class VII of SMPLB SLB Islam Qothrunnada. The data come from pre-test and post-test assessments (n = 4), classroom observations, learning documentation, and teacher reflections. The results show an increase in the average reading comprehension score from 50 (pre-test) to 82.5 (post-test). These findings support the effectiveness of MMR in improving meaningful literacy in deaf students, aligning with general evidence that structured and dialogic language interventions enhance language skills and comprehension in the DHH (deaf and hard-of-hearing) population. Practical implications, limitations, and recommendations for replication are detailed.